2015
DOI: 10.1016/j.ijcard.2015.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum leptin with future left ventricular structure and function: The Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Background/Objectives Earlier studies differ on whether serum leptin is associated with adverse or beneficial cardiac structure. We determined the association between serum leptin with subsequent cardiac structure and function. Methods Multicenter longitudinal study of Black, White, Hispanic and Asian-American men and women. Cardiac MRI (CMR) was completed 6 to 8 years after leptin was measured. Left ventricular (LV) mass and volumes were indexed to body surface area. Multivariable linear regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, investigators have related circulating concentrations of adipokines to imaging indices of cardiac remodeling. These prior studies have typically been conducted in small samples, or samples with an overrepresentation of obese individuals or elderly people, and usually focused on a single adipokine 10, 11, 13, 21, 22, 23, 24, 25, 26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adipokines are the bioactive products of adipose tissue [1] and are recognised as important regulators of food intake, body metabolism and insulin resistance [2]. Adipokines are also known to affect the vascular wall and the human heart in an endocrine manner through the systemic circulation or even in a paracrine manner via their release from local depots such as perivascular or epicardial adipose tissue [3,4].…”
mentioning
confidence: 99%